Introducción. 1806 y doscientos años más: Moratín poliédrico - Nava Rodríguez, Teresa (Cuadernos de Historia Moderna, 2008)
This introduction describes the circumstances surrounding the celebration in Madrid, on 13th and 14th December, 2006, of the International Conference Social change and literary fiction in Moratin’s Spain. It also contains a scientific justification for the work and a preview of its contents.